2016
DOI: 10.1016/j.ijid.2016.11.193
|View full text |Cite
|
Sign up to set email alerts
|

Seropositivity of delta hepatitis in patients with positive hepatitis B surface antigen, between 2011 and 2016

Abstract: Results: From 2000-2015 a total of 57 cases of tularemia were reported in Armenia. Of these, 84.2% were male and 78.9% were from rural areas. Distribution of age groups were: ≤18-24.6%, 19-30-54.4%, 31-44-14.01%, ≥45-7.0%. The most common symptoms include: fatigue (n=52, 91%), fever (n=45, 78.9%), pharyngitis (n=40, 70.2%), headache (n=27, 47.4%), hepatomegaly (n=5, 8.8%), and splenomegaly (n=2, 3.5%). The average hospitalization stay was 35.7 days. The most frequent clinical forms were bubonic (n=28, 49.1%), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…During the study period of 35 years, 111 publications were found 13–123 . Among inactive HBV carriers, 34 studies reported HDV prevalence and it did not change significantly over three decades 6,13–45 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the study period of 35 years, 111 publications were found 13–123 . Among inactive HBV carriers, 34 studies reported HDV prevalence and it did not change significantly over three decades 6,13–45 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…(Table 2). Seventeen studies included all HBsAg‐positive patients without further describing patients' characteristics and reported decreasing (from Period 1 to Period 2, 7.0%–3.0%) and then increasing (from Period 2 to Period 3, to 4.7%) HDV prevalence 6,66–81 . Cumulative data of these three groups were taken to reveal HDV prevalence in HBV‐infected patients, and it showed decreasing (from Period 1 to Period 2) followed by increasing (from Period 2 to Period 3) HDV prevalence (Table 3 and Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Çalışmamızda, 1.831 HBsAg pozitif hastanın 66'sında (%3.6) delta antikoru saptanmıştır. Buna göre, Edirne'de 2016 yılında yapılan ve HBsAg pozitif hastalarda HDV seroprevalansının %2.47 olarak tespit edildiği bir çalışmaya oranla, delta antikor pozitifliğinde hafif bir yükselme gözlenmektedir (20) . Bununla birlikte, ülkemizde yapılan benzer çalışmalar ile karşılaştırıldığında, yüksek seroprevalansa sahip belirli bölgeler dışında bu oranın Türkiye geneliyle uyumlu olduğu görülmektedir.…”
Section: Discussionunclassified